Adaptation through Collaboration: Developing Novel Platforms to Advance the Delivery of Advanced Therapies to Patients - Papadaki, Magdalini (Frontiers in Medicine, 2017)
For the nascent field of advanced therapies, collaboration will be a game-changer, turning scientific progress that was once unimaginable into transformative medical practice. Despite promise for life-long management and even cure of disease, scepticism remains about the feasibility of their delivery to patients, fuelling investment risks. With the potential for long-term effectiveness in need of frequent re-assessment, current approaches to predict real-life drug performance bear little relevance, necessitating novel and iterative schemes to monitoring the benefit-risk profiles throughout the lifespan of advanced therapies. This work explains that reinventing an adoption route for ATMPs is as much about the scientific and clinical components, as it is about the organizational structures, requiring an unprecedented level of interactions between stakeholders not traditionally connected; from developers and regulators, to payers, patients and funders. By reflecting on the successes and lessons learned from the growing space of global precompetitive consortia and public-private partnerships (PPPs), as well as a number of emerging accelerated development pathways, this work aims to inform the foundations for a future roadmap that can smooth the path to approval, reimbursement and access, while delivering value to all stakeholders. Echoing the growing demands to bring these transformative products to patients, it provides critical insights to enhance our capacity in three fundamental domains: deploying the operational flexibilities offered by the growing space of collaborations, utilizing emerging flexible and accelerated pathways to tackle challenges in quantifying long-term effectiveness, and building the necessary digital and clinical infrastructure for knowledge development.